Control Schemes for Reducing Second Harmonic Current in Two-Stage Single-Phase Converter: An Overview From DC-Bus Port-Impedance Characteristics - Zhang, Li; Ruan, Xinbo (IEEE transactions on power electronics, 2019)
The instantaneous input and output power of two-stage single-phase converter are imbalanced, resulting in the second harmonic current (SHC) in the dc-dc converter, dc source, or dc load. This paper revisits the SHC reduction control schemes from the dc-bus port-impedance perspective. The dc-dc converters in two-stage single-phase converters are categorized into two types, namely, bus-voltage-controlled converter (BVCC) and bus-current-controlled converter (BCCC). The dc-bus port impedance of the BVCC is revealed to be approximately inversely proportional to the voltage loop gain. Thus, for reducing the SHC in the BVCC, advanced control schemes are required for increasing the dc-bus port impedance. The dc-bus port impedance of the BCCC is proved to be a negative resistor within the control bandwidth. Hence, for reducing the SHC in the BCCC, the dc-bus voltage ripple should be limited. From the dc-bus port-impedance perspective, the SHC reduction control schemes are reclassified into closed-loop-design-based, virtual-impedance-based, and power-decoupling-based approaches, based on which, different SHC reduction control schemes are carefully reviewed and compared. Finally, potential challenges and issues are discussed.